Interaksi Sosial Dalam Pembinaan Renang Pada Klub Aqualux Garut - Ani Kurniawati; Z. Arifin; Hazkia Yunaira (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2026)
Sports coaching is not only influenced by the technical aspects of training, but also by the quality of social interactions between coaches, athletes, and parents. However, studies on social interactions in swimming coaching at the club level, particularly those involving these three parties, are still limited. This study aims to describe social interactions in swimming coaching at the Aqualux Garut Club using the 3+1Cs model (Closeness, Commitment, Complementarity, Co-orientation). The research method used was an ex-post facto study with a descriptive qualitative approach. The sample consisted of 10 athletes, 2 coaches, and 2 parents who were selected purposively. The research instruments were a 3+1Cs model questionnaire that had been tested for validity and reliability, and semi-structured interviews. The results showed that social interactions were in the very good category (average 81.5%), with the highest score in the Complementarity dimension (84%), followed by Closeness (83%), Commitment (81%), and Co-orientation (78%). Interviews corroborated the questionnaire findings, demonstrating emotional closeness, commitment, harmonious cooperation, and alignment of goals, although some athletes were still reluctant to express their opinions. The study concluded that positive social interactions play a crucial role in supporting athletes' skills, motivation, and mental well-being.